Cretaceous spreite-dominated ichnoassemblages in Antarctica - DANIEL SEDORKO; CAROLINA GUTIÉRREZ; PABLO J. PAZOS; JAMES H. NEBELSICK; LUIZ CARLOS WEINSCHÜTZ; MARIANA ALMEIDA GOMES GARCIA; RODRIGO CARDOSO; JULIANA MANSO SAYÃO; ALEXANDER W.A. KELLNER (Anais da Academia Brasileira de Ciências)
Abstract This study investigates ichnoassemblages characterized by spreite trace fossils from the Upper Cretaceous Snow Hill Island Formation on Vega Island, Antarctica. The succession reveals alternating heterolithic beds of sandy siltstones to very fine- to fine-grained sandstones, suggestive of a deltaic depositional setting influenced by fluctuating energy conditions. The dominance of spreite structures, such as Paradictyodora antarctica and Euflabella, suggests the prevalence of a colonization window for deposit- or detritus-feeding activity. Notably, the prevalence of Euflabella towards the upper levels of the succession, in more proximal and impacted depositional setting, suggests an adaptive strategy for coping with varying food resources, corroborating its role as a trophic generalist. Additionally, the absence of distinct shifts between fully marine and stressed ichnofauna challenges a clear assignation to the Phycosiphon or Rosselia ichnofacies, although in vertical succession the Euflabella dominance in upper levels is related to a lower diverse ichnoassemblage than Paradictyodora in lower levels, suggesting some freshwater impact in the top. The occurrence of horizontal and vertical sessile deposit feeding structures would align with the Rosselia ichnofacies definition, but the presence of spreite burrows and high ichnodisparity better fits into the Cruziana ichnofacies. These spreite-dominated ichonoassemblages are here attributed to Cruziana ichnofacies.